2018
DOI: 10.1017/s0014479718000108
|View full text |Cite
|
Sign up to set email alerts
|

COFFEA CANEPHORA CLONES WITH MULTIPLE RESISTANCE TO MELOIDOGYNE INCOGNITA AND M. PARANAENSIS

Abstract: SUMMARYRoot-knot nematodes represent a serious threat to world coffee production, especially Meloidogyne incognita and M. paranaensis. Most cultivars of Coffea arabica are highly susceptible to these parasites and cultivation in infested areas has only been possible with the use of resistant C. canephora rootstocks. In this research, three elite clones of C. canephora, selected in areas infested by M. incognita and M. paranaensis, were evaluated in controlled conditions to assess levels of resistance against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…Both are resistant to M. exigua but with different levels of resistance segregation to M. incognita and M. paranaensis. A more recent study identified clones of C. canephora with multiple resistance to M. incognita and M. paranaensis (Fatobene et al, 2018) that could be used in the breeding of new rootstocks or ungrafted cultivars of C. canephora. Currently, some ungrafted cultivars of C. arabica resistant to RKNs are available, such as IPR 100 resistant to M. paranaensis (Sera et al, 2007) and to M. exigua (Rezende et al, 2017), and IAC 125 RN (Fazuoli et al, 2018) and IAPAR 59 (Salgado et al, 2005) resistant to M. exigua.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are resistant to M. exigua but with different levels of resistance segregation to M. incognita and M. paranaensis. A more recent study identified clones of C. canephora with multiple resistance to M. incognita and M. paranaensis (Fatobene et al, 2018) that could be used in the breeding of new rootstocks or ungrafted cultivars of C. canephora. Currently, some ungrafted cultivars of C. arabica resistant to RKNs are available, such as IPR 100 resistant to M. paranaensis (Sera et al, 2007) and to M. exigua (Rezende et al, 2017), and IAC 125 RN (Fazuoli et al, 2018) and IAPAR 59 (Salgado et al, 2005) resistant to M. exigua.…”
Section: Discussionmentioning
confidence: 99%
“…The use of resistant cultivars is the best way to cultivate coffee plants in soils infested by RKNs. While most of C. arabica cultivars are susceptible to M. paranaensis, C. canephora shows genetic variability in their resistance to this nematode species (Bertrand et al, 2000;Fatobene et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Ferraz (2018) and Ventura et al (2019) the strategies to reduce the population of phytonematodes in field are biological, chemical and genetic, the latter being the most efficient and economically viable. Therefore, the selection of resistant clones is one of the most promising alternatives to minimize the damage caused by nematodes in the coffee culture, keeping the nematode populations below the level of economic damage (Fatobene et al, 2018;Rezende et al, 2019;Salgado et al, 2020). The clones BRS 3210, C12, BRS 2314, BRS 3137 and BRS 1216, showed resistance to M. incognita.…”
Section: Resultsmentioning
confidence: 99%
“…Plant-parasitic nematodes have an important economic impact on coffee in most coffeeproducing countries. Economic losses may vary considerably, depending on the species, the population density and the susceptibility of the host cultivar (Fatobene et al, 2018). Among the most harmful species are the Meloidogyne exigua Göldi 1887, M. incognita (Kofoid & White) Chitwood 1949 and M. paranaensis Carneiro, Almeida and Carneiro (1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation